1953
DOI: 10.1002/jcp.1030410103
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic nutrition of Saccharomyces cerevisiae. I. Ergosterol requirement for growth in a defined medium

Abstract: Past work in this laboratory has shown that the stationary populations of 8. cerevisiae produced in a yeast extract medium during serial transfer under continuous anaerobic conditions mere quite small, while excellent growth occurred in the presence of oxygen (Brockmann and Stier, '47). It was also shomm that the anaerobic population could be greatly increased by supplementing the medium with various crude materials, such as vegetable oils, malt sprouts and distillers' dried solubles, or their unsaponifiable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
204
0
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(207 citation statements)
references
References 16 publications
2
204
0
1
Order By: Relevance
“…Although cells growing on rich medium can typically undergo several (two to three) anaerobic divisions without supplementation, an exogenous source of unsaturated fatty acids and sterol is essential for long-term anaerobic growth (3,4). One of the most striking patterns in gene expression observed during anaerobic growth is the remodeling activity associated with the cell wall and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cells growing on rich medium can typically undergo several (two to three) anaerobic divisions without supplementation, an exogenous source of unsaturated fatty acids and sterol is essential for long-term anaerobic growth (3,4). One of the most striking patterns in gene expression observed during anaerobic growth is the remodeling activity associated with the cell wall and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids and sterols. Although it has long been known that an exogenous source of unsaturated fatty acid and sterol is essential for long-term anaerobic growth in S. cerevisiae (3,4), a more complete picture of the anoxia-induced remodeling in these pathways is revealed here. Notably, this remodeling is fairly specific for sterol and sphingolipid pathways, with very few genes for phospholipid or fatty acid synthesis (save for AAC1 and OLE1) showing changes in expression.…”
Section: Vol 25 2005 Genomic Response Of Yeast To Anaerobiosis 4085mentioning
confidence: 93%
“…In fact, with the notable exception of Saccharomyces cerevisiae, none of the type species of the 75 yeast genera are able to grow under strictly anaerobic conditions with specific growth rates higher than 0.10 h -1 (Visser et al 1990). Even in the case of S. cerevisiae, anaerobic growth conditions impose additional growth factor requirements (in particular ergosterol, nicotinic acid and unsaturated fatty acids; Andreasen & Stier 1953, 1954Schatzmann 1975). The biosynthesis of these compounds involves oxygenation reactions and they therefore have to be included in the growth medium to allow anaerobic growth.…”
Section: Effects Of Oxygen On Growth Kineticsmentioning
confidence: 99%
“…In this connection it has been reported that this effect is not caused by insufficiency of ergosterol in the medium, but rather reflects a diminished requirement for crgosterol under anaerobic growth owing to lack of normal mitochondrial structures. 1 The concentration of long-chain unsaturated fatty acids in lipid-dcplcted cultures follows a pattern similar to that of ergosterol during anaerobic conditions. (Table I).…”
Section: Resultsmentioning
confidence: 95%